2020
DOI: 10.18203/2319-2003.ijbcp20200174
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of knowledge, attitude and practices on antibiotic resistance among undergraduate medical students in the school of medicine at the University of Zambia

Abstract: Background: The issue of antibiotic resistance has become a global public health concern, with an extensive clinical and economic burden. The study aimed to assess the knowledge, attitude, and practices of antibiotic resistance among undergraduate medical students at the University of Zambia.Methods: This cross-sectional study was conducted at the University of Zambia Ridgeway Campus. A structured questionnaire was administered to 260 randomly selected undergraduate medical students. Data were analyzed using S… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
32
3

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
1

Relationship

5
4

Authors

Journals

citations
Cited by 42 publications
(43 citation statements)
references
References 32 publications
(52 reference statements)
3
32
3
Order By: Relevance
“…Therefore, pharmacists must continue playing the role of gatekeepers of antibiotics [116]. Educational interventions must be put in place to improve the appropriate prescribing and dispensing of antibiotics [117][118][119].…”
Section: Attitudes Of Community Pharmacists Towards Antibiotic Resistmentioning
confidence: 99%
“…Therefore, pharmacists must continue playing the role of gatekeepers of antibiotics [116]. Educational interventions must be put in place to improve the appropriate prescribing and dispensing of antibiotics [117][118][119].…”
Section: Attitudes Of Community Pharmacists Towards Antibiotic Resistmentioning
confidence: 99%
“…The inappropriate prescribing of antibiotics for common diseases in paediatric patients has also contributed to an increase in ABR [6]. Irrational and inappropriate use of antibiotics has contributed largely to the development of antibiotic resistance (ABR) [7,8].…”
Section: Introductionmentioning
confidence: 99%
“…25 Concerning knowledge, 68% of the study subjects were knowledgeable about antibiotics and antibiotic resistance, which is higher than the study findings from Amman, Jordan (23%), and Kuwait (47%), 17,27 while it is lower than the study finding from the University of Zambia (87.3%). 28 The discrepancy might be due to the reason that the study subjects of Zambia University were only medical students. In this study, it was found that the students who have a family member employed in health and related areas had a higher probability of taking a full course of antibiotic treatment, which is supported by existing evidence in Italy.…”
Section: Discussionmentioning
confidence: 99%